SmartGrowth - An Intelligent Environmental Control and Alert Mechanism System - Shaout, Adnan; Sriram, Gnana; Solleti, Venkata (Journal of Engineering Research and Reviews, 2025)
Smart agriculture is an emerging technology that offers a promising solution to improve the efficiency of crop growth. Our project aims to create a smart agriculture system that leverages technology to improve crop growth and yield, decrease costs, and minimize environmental impact. The proposed system will monitor key environmental factors, including temperature, humidity, soil moisture, and light, to optimize crop growth. The proposed hardware system will utilize the STM32 microcontroller and the FreeRTOS for environmental control and monitoring, and it will alert farmer in case of any irregularities. The proposed smart agriculture system has the potential to enhance resource efficiency, increase profitability, and improve crop production.